2016
DOI: 10.21082/jpptp.v35n2.2016.p125-132
|View full text |Cite
|
Sign up to set email alerts
|

Stabilitas Hasil Jagung Varietas Hibrida Harapan Umur Genjah

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…This position of ear plant was suitable for selected of superior population included anthocyanins corn. The result experiment [15] [16] reported that selection of plant with ear position in middle from plant height could founded maximal yield. Variety grain white of opv Anoman 1 be founded 6-7 t/ha with ear height 90 cm and plant height 182 cm in dry environment like in Palu.…”
Section: Interaction Analysis G X Smentioning
confidence: 99%
“…This position of ear plant was suitable for selected of superior population included anthocyanins corn. The result experiment [15] [16] reported that selection of plant with ear position in middle from plant height could founded maximal yield. Variety grain white of opv Anoman 1 be founded 6-7 t/ha with ear height 90 cm and plant height 182 cm in dry environment like in Palu.…”
Section: Interaction Analysis G X Smentioning
confidence: 99%
“…Gen-gen yang beragam dari masing-masing varietas tervisualisasikan pada karakter-karakter yang beragam (Isnaini et al, 2019). Perbedaan beberapa karakter pertumbuhan jagung dipengaruhi oleh ekspresi masing-masing gen yang yang berbeda walaupun dalam lingkungan yang sama (Maruapey, 2012), perbedaan genotipe dan responnya terhadap lingkungan sehingga berpengaruh terhadap kemampuan beradaptasi pada lingkungan tumbuh yang baru (Iriany et al, 2018;Soleymani, 2017) serta interaksi antara genotip dan lingkungan (Andayani, 2014;Priyanto et al, 2016). Perbedaan karakter pertumbuhan jagung selain dipengaruhi oleh genetik juga dipengaruhi oleh agroklimat lokasi budidaya.…”
Section: Jumlah Tongkol Per Hektarunclassified